2019
DOI: 10.1634/theoncologist.2018-0921
|View full text |Cite
|
Sign up to set email alerts
|

TELEPRO: Patient-Reported Carcinoid Syndrome Symptom Improvement Following Initiation of Telotristat Ethyl in the Real World

Abstract: Patients with carcinoid syndrome diarrhea that is not controlled with long‐acting somatostatin analogs can benefit from the addition of the tryptophan hydroxylase inhibitor, telotristat ethyl. This article evaluates the real‐world effectiveness of telotristat ethyl using patient‐reported data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 15 publications
3
23
0
Order By: Relevance
“…
We read with great interest the recent work by Strosberg et al reporting on the results of the TELEPRO study [1]. This study highlights the benefit of telotristat ethyl in improving other symptoms of carcinoid syndrome as well as diarrhea.
…”
mentioning
confidence: 69%
“…
We read with great interest the recent work by Strosberg et al reporting on the results of the TELEPRO study [1]. This study highlights the benefit of telotristat ethyl in improving other symptoms of carcinoid syndrome as well as diarrhea.
…”
mentioning
confidence: 69%
“…Improvements in CS symptoms and health indicators were consistent with those from other real-world studies of TE. 11,12,19 The TELEPRO real-world study showed improvements in CS symptoms through 3 months of TE treatment, including improvements among those with a relatively low burden of CSD (≤3 daily bowel movements). 11,19 The RELAX registry showed 75% of patients to have maintained or gained weight after 6 months of TE treatment (22% reported weight gain).…”
Section: Discussionmentioning
confidence: 99%
“…11,12,19 The TELEPRO real-world study showed improvements in CS symptoms through 3 months of TE treatment, including improvements among those with a relatively low burden of CSD (≤3 daily bowel movements). 11,19 The RELAX registry showed 75% of patients to have maintained or gained weight after 6 months of TE treatment (22% reported weight gain). 12 We observed weight maintenance or gain in 86% of patients (28% weight gain) over an average of 12 months of TE treatment in the overall TELEACE population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Telotristat ethyl is a prodrug that is converted into its active metabolite telotristat etiprate after oral administration (22). In CS patients, telotristat ethyl has been associated with significant improvement in the symptoms of CS, including diarrhea, over 1-3 mo, of therapy (23). In addition, in the TELESTAR study in patients with CS, treatment with telotristat ethyl was associated with significant, dose-dependent weight gain and reduced severity of diarrhea in approximately one-third of cases (24).…”
Section: Treatment Of Csmentioning
confidence: 99%